Using task-based language teaching in teaching reading comprehension for EFL learners - Nastiti, Diah Bunga; Yasin, Burhanuddin; Muslem, Asnawi (Research and Innovation in Language Learning, 2023)
Task-Based Language Teaching is considered effective method in improving students reading comprehension ability. This research aimed at finding out the effect of Task-Based Language Teaching on students reading comprehension skill and also in the summarizing, making inference, and interpreting vocabulary aspect of reading comprehension The approach used in this research was the quantitative method and applying the true experimental research. The research sample was 64 students of grade XII at <span lang="IN" style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">M<span style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">adrasah <span lang="IN" style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">A<span style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">liyah <span lang="IN" style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">N<span style="font-size: 12.0pt; mso-bidi-font-size: 21.0pt; line-height: 115%; font-family: 'inherit','serif'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Courier New'; color: #202124; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">egeri (MAN) 1 Aceh Barat who are divided into experimental and control class. The researcher used reading comprehension test question to obtain the data. Based on the research result and data analysis using SPSS 23, the result showed a significant difference on post-test result between experimental class and control class. Thus, the alternative hypothesis in this research was accepted. The improvement also occurred in summarizing, making inference, and interpreting vocabulary aspect. Therefore, it is recommended that the teachers employ Task-Based Language Teaching in teaching reading comprehension. Task-Based Language Teaching is advantageous in improving the students reading comprehension skill.